2006
DOI: 10.1063/1.2220564
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal dispersions of octadecyl grafted silica spheres in toluene: A global analysis of small angle neutron scattering contrast variation and concentration dependence measurements

Abstract: In this paper we report measurements of the form factor and the structure factor of a sterically stabilized colloidal dispersion consisting of silica spheres coated with octadecane in toluene by small angle neutron scattering ͑SANS͒. The phase diagram of this system shows the liquid-liquid coexistence line and also a jamming transition at higher concentrations, where the jamming line intersects the coexistence line roughly at the critical point. We have performed SANS experiments at a temperature well above th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 36 publications
6
30
1
1
Order By: Relevance
“…At the temperature of the present study, the colloidal suspension acts like a hardsphere fluid, as has been shown in Ref. [24] for the present batch of the suspension. This also provides support for using hard-sphere interactions in the theoretical calculations.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…At the temperature of the present study, the colloidal suspension acts like a hardsphere fluid, as has been shown in Ref. [24] for the present batch of the suspension. This also provides support for using hard-sphere interactions in the theoretical calculations.…”
mentioning
confidence: 58%
“…and q k denoting the out-of-plane and in-plane components of the scattering vector, respectively. In order to facilitate the comparison between experiment and theory, we have determined the experimental SðqÞ within the monodisperse approximation, which is a reasonable approximation for the present colloidal suspension [24]. The agreement between experimental and theoretical data is striking.…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 20 Januamentioning
confidence: 99%
See 1 more Smart Citation
“…We first consider the case with a structure factor S(q) = 1, namely, dilute solutions. The total scattering intensity of a monodisperse system I(q) is given by [30][31][32]49] …”
Section: Dynamic Light Scatteringmentioning
confidence: 99%
“…Using the EHS or HPY potential, particle interactions of bare or polymer-coated colloids have been systematically explored for a variety of colloidal dispersions [5,32,[39][40][41][42][43][44]. Another semi-empirical potential often employed for analyzing the structure factor of adhesive colloidal particles is the square-well (SW) potential [8,45,46] or the stickyhard-sphere (SHS) potential [47][48][49], which has stemmed from the Baxter's sticky potential [50] describing the van der Waals (vdW) attractions between spherical particles. The structure factor for the SW potential has also been derived using the Percus-Yevick closure [51].…”
Section: Introductionmentioning
confidence: 99%